A LONG CHAIN ALCOHOL AND TWO STEROL COMPOUNDS FROM THE HEXANE EXTRACT OF STEM BARK OF Aglaia odorata Lour. (Meliaceae) - Tukiran Tukiran; Prima Ardhiana; Suyatno Suyatno; Kuniyoshi Shimizu (Universitas Gadjah Mada, 2008)
A long chain alcohol, 1-eicosanol together with two sterols, β-sitosterol and stigmasterol had been isolated from hexane extract of stem bark of pacar cina (Aglaia odorata Lour) (Meliaceae). These structures had been established based on spectroscopic data (IR and NMR) and by comparison to those of standard compounds.